Summer PM2.5 Pollution Extremes Caused by Wildfires Over the Western United States During 2017–2018. Issue 16 (17th August 2020) - Xie, Yuanyu; Lin, Meiyun; Horowitz, Larry W.
Abstract: Using observations and model simulations (ESM4.1) during 1988–2018, we show large year‐to‐year variability in western U.S. PM2.5 pollution caused by regional and distant fires. Widespread wildfires, combined with stagnation, caused summer PM2.5 pollution in 2017 and 2018 to exceed 2 standard deviations over long‐term averages. ESM4.1 with a fire emission inventory constrained by satellite‐derived fire radiative energy and aerosol optical depth captures the observed surface PM2.5 means and extremes above the 35 μg/m 3 U.S. air quality standard. However, aerosol emissions from the widely used Global Fire Emissions Database (GFED) must be increased by 5 times for ESM4.1 to match observations. On days when observed PM2.5 reached 35–175 μg/m 3, wildfire emissions can explain 90% of total PM2.5, with smoke transported from Canada contributing 25–50% in northern states, according to model sensitivity simulations. Fire emission uncertainties pose challenges to accurately assessing the impacts of fire smoke on air quality, radiation, and climate. Plain Language Summary: Frequent and intense wildfires harm public health over the western United States. In order to understand how wildfires affect fine particulate air quality, we analyze surface and satellite measurements and computer model simulations of weather and atmospheric chemistry over the past 30 years. We show that widespread fires and regional transport of fire smoke are the main causes of year‐to‐year changes in summertime particle pollution measured at western U.S. surface sites. The U.S. Environmental Protection Agency defines daily particle concentration above 35 μg/m 3 as unhealthy. In the summers of 2017–2018, record‐breaking wildfires, combined with stable weather conditions, resulted in daily particle concentration of 35 to 175 μg/m 3 across western U.S. sites. These particle pollution extremes are twice as severe as long‐term average conditions. Wildfire emissions contributed 90% of particle levels on these periods. Notably, transport of fire smoke from southwestern Canada can explain 25% to 50% of particle pollution in northern states such as Washington. Our model successfully simulates these pollution extremes when applying a fire emission data set constrained by satellite observations of total particle abundances. Our results indicate fourfold to fivefold underestimates of particle emissions from the widely used Global Fire Emissions Database not constrained by satellite observations. Key Points: Large interannual variations of western U.S. fine particulate pollution in summer were driven by regional and distant fires Widespread wildfires and stagnation in 2017–2018 caused fine particulate extremes to exceed 2 standard deviations over long‐term averages Observations and model analyses indicate fourfold to fivefold underestimate of aerosol emissions from the widely used Global Fire Emissions Database